Driving Change The Story of the South Africa Norway Tertiary Education Development Programme - Gibbon, Trish; Project Muse; Project Muse. (Project Muse, 2014)
Driving Change tells a story that exemplifies a basic law of physics, known to all ñ the application of a relatively small lever can shift weight, create movement and initiate change far in excess of its own size. It tells a story about a particular instance of development cooperation, relatively modest in scope and aim that has nonetheless achieved remarkable things and has been held up as an exemplar of its kind. It does not tell a story of flawless execution and perfectly achieved outcomes: it is instead a narrative that gives some insight into the structural and organisational arrangements.
Acronyms -- About the authors -- The editorial group -- Preface -- Introduction -- Chapter 1. Promoting South African reform objectives through development cooperation -- Chapter 2. The Norwegian perspective -- Chapter 3. The role of the SANTED Secretariat: Riding the development cooperation bicycle, hands on and hands off -- Chapter 4. Supporting and enhancing the academic project: Improving student throughput and success within an equity framework -- Chapter 5. Multilingualism for teaching and learning -- Chapter 6. Challenges relating to the establishment of comprehensive universities in the South African higher education sector -- Chapter 7. Cross-border collaboration in the Southern African Development Community countries -- Conclusion -- References.
Issued as part of book collections on Project MUSE.
Includes bibliographical references (pages [162]-168).
Description based on print version record.
Keywords: Educational change -- Norway; Educational change -- South Africa; Higher education -- Norway; Higher education -- South Africa; Electronic books; Electronic books